PENERAPAN PRINSIP KEBEBASAN BERKONTRAK DALAM KONTRAK STANDAR PENGADAAN BARANG DAN JASA PEMERINTAH DI INDONESIA - Muskibah Muskibah; Lili Naili Hidayah (Universitas Kristen Satya Wacana, 2020)
Freedom of contract is not a freedom without limits. Standard form of contract for the procurement of goods and services of the government is one of the limitations of the freedom of contract. Formulation and arrangement of rights and obligations contained in the contract for the procurement of goods and services are based on the standard regulation as embedded in the Standard Document Procurement/ Electronic Standard Document Procurement. This research aims to analyze the validity of the freedom of contract principle in standard contract or adhesion contract as well as forms of the freedom of contract in the standard contract for the procurement of government goods and services. This research is a juridical and normative legal research. This research discovered that the standard contract/adhesion contract contradicts with the freedom of contract principle, and it is established that the freedom of contract can be found in the standard contract for the procurement of government goods and services at the pre-contractual stage. At the contractual and post-contractual stages freedom of contract is only an implementation of the provisions of the law. Therefore, this research recommends that it is necessary to change the provision on the rights and obligations of the parties at the pre-contractual stage, contractual stage, as well as post-contractual stage.